Czasowe zajęcie zabytku ruchomego. Uwagi de lege lata i de lege ferenda: [The temporary seizure of a movabke monument. Remarks de lege lata and de lege ferenda] (Studia Prawnicze / The Legal Studies, 2017)
Celem niniejszego artykułu jest wykazanie, że instytucja czasowego zajęcia zabytku ruchomego stanowi przykład środka nadzoru konserwatorskiego o jednym z największych stopni ingerencji w prawo własności zabytku w polskim porządku prawnym. Ponadto celem niniejszego artykułu jest odpowiedź na pytanie, czy możliwość czasowego zajęcia zabytku ruchomego skutkuje cał-kowitym pozbawieniem prawa własności zabytku ruchomego? W końcu słusz-nym wydaje się udzielenie odpowiedzi na pytanie, czym różni się czasowe zajęcie od przejęcia zabytku ruchomego na kanwie obowiązujących przepisów prawa? W oparciu o metodologię dogmatyczną oraz historyczną dokonano porównania historycznych aktów prawnych dotyczących problematyki czasowego zajęcia zabytku ruchomego jako jednego ze środków nadzoru konserwatorskiego w polskim systemie prawnym. This article provides an in-depth analysis of the problem of the temporary seizure of a movable monument in the Polish law. One of the purposes of this text is to prove that the institution of the temporary seizure of a movable monument is an example of the measure of a conservation supervision with one of the highest levels of interference in the ownership of monument in the Polish legal system. Currently the issues related to the temporary seizure of a movable monument are regulated by the act on the protection and guardianship of monuments. The first legal act which regulated these issues was the decree of the Regency Council on the protection of monuments of art and culture of 31 October 1918. The analysis of the historical legal acts, as well as legal acts in force, proved that temporary seizure of a monument resulted in a temporary loss of possession and use of a particular monument. However, this measure of a conservation supervision is not an ultima ratio measure, which deprives the ownership of movable monument in a complete manner.